Resolution of financial distress: A theory of the choice between Chapter 11 and workouts - John, Kose; Mateti, Ravi S.; Vasudevan, Gopala (Journal of Financial Stability, 2013)
We model the reorganization decision of distressed firms. One of the novel features of our paper is that we examine the asset and liability side restructuring decisions jointly to resolve financial distress. Secondly, we model several institutional features of coping with financial distress such as debtor-in-possession financing, prepackaged bankruptcies, and asset sales. In our model, asset liquidity, indirect costs of financial distress, and the option value of equity are the determinants of the choice between Chapter 11 reorganizations and workouts. The model develops several testable predictions, some of which are novel and others of which are able to explain previously documented empirical results.